The urban strategy of Pope Paul III. The conclusion of the Trident of Piazza del Popolo (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2025)
During the sixteenth and seventeenth centuries, the transformation of Rome promoted by the Papal Government aimed not only to answer to the needs of a modern state but also to represent the Papacy as an absolute monarchy. The visit of Emperor Charles V in 1536 became the opportunity to improve urban connections and to build architectural complexes such as the Capitoline Hill. The importance of these places was highlighted by putting them at the head of new streets: Pope Paul III made the Capitol visible from Via del Corso, renovated in 1538 as a part of the Campo Marzio general urban plan. If Pope Leo X imagined two streets (Via del Corso and the new Via di Ripetta) leading into the square in front of Porta del Popolo, and Clement VII began the third axis, it was Paul III who should be properly considered as the inventor of the trident of Piazza del Popolo. On the other hand, the pope experimented with the employment of straight roads that organized the territory as symbols of power also in his residence in Caprarola, an effective laboratory of absolutism.Keywords: Rome, Pope Paul III, Emperor Charles V, the Trident, urban strategies.